(untitled) (Лучшие интеллектуальные исследования, 2025)
Annotation: Tuition fees at German federal institutions of higher education are virtually non-existent, and only small administration fees have to be paid by students. What remains to be covered are expenses for basic needs and accommodation. Among several options to finance living expenses, students can receive financial help from their parents, work to earn their own income, or apply for scholarships and student federal aid, also known as BAföG, which is provided by the Federal Training Assistance Act (Bundesausbildungsförderungsgesetz).